Algorithms for Finding Global Minimizers of Image Segmentation and Denoising Models - Chan, Tony F.; Selim Esedoḡlu; Nikolova, Mila (SIAM journal on applied mathematics, 2006)
We show how certain nonconvex optimization problems that arise in image processing and computer vision can be restated as convex minimization problems. This allows, in particular, the finding of global minimizers via standard convex minimization schemes.